Student- and school-level factors associated with mental health and well-being in early adolescence - Hinze, V; Montero-Marin, J; Blakemore, S-J; Byford, S; Dalgleish, T; Esposti, MD; Greenberg, MT; Jones, BG; Slaghekke, Y; Ukoumunne, OC; Viner, RM; Williams, JMG; et al. (Elsevier, 2023)
Objective: Adolescence is a key developmental window that may determine long-term mental health. As schools may influence mental health of students, this study aimed to examine the association of school-level characteristics with students’ mental health over time. Method: Longitudinal data from a cluster randomized controlled trial comprising 8,376 students (55% female; aged 11-14 years at baseline) across 84 schools in the United Kingdom were analyzed. Data collection started in the academic years 2016/2017 (cohort 1) and 2017/2018 (cohort 2), with follow-up at 1, 1.5, and 2 years. Students’ mental health (risk for depression [Center for Epidemiologic Studies Depression Scale], social-emotional-behavioral difficulties [Strength and Difficulties Questionnaire]) and well-being (Warwick-Edinburgh Mental Well-Being Scale) and relationships with student- and school-level characteristics were explored using multilevel regression models. Results: Mental health difficulties and poorer well-being increased over time, particularly in girls. Differences among schools represented a small but statistically significant proportion of variation (95% CI) in students’ mental health at each time point: depression, 1.7% (0.9%-2.5%) to 2.5% (1.6%-3.4%); social-emotional-behavioral difficulties, 1.9% (1.1%-2.7%) to 2.8% (2.1%-3.5%); and well-being, 1.8% (0.9%-2.7%) to 2.2% (1.4%-3.0%). Better student-rated school climate analyzed as a time-varying factor at the student and school level was associated with lower risk of depression (regression coefficient [95%CI] student level: −4.25 [−4.48, −4.01]; school level: −4.28 [−5.81, −2.75]), fewer social-emotional-behavioral difficulties (student level: −2.46 [−2.57, −2.35]; school level: −2.36 [−3.08, −1.63]), and higher well-being (student level: 3.88 [3.70, 4.05]; school-level: 4.28 [3.17, 5.38]), which was a stable relationship. Conclusion: Student-rated school climate predicted mental health in early adolescence. Policy and system interventions that focus on school climate may promote students’ mental health.